Commercially available antibodies can be applied in quantitative multiplexed peptide immunoaffinity enrichment targeted mass spectrometry assays. Issue 15 (23rd May 2016) - Schoenherr, Regine M.; Zhao, Lei; Ivey, Richard G.; Voytovich, Uliana J.; Kennedy, Jacob; Yan, Ping; Lin, Chenwei; Whiteaker, Jeffrey R.; Paulovich, Amanda G.
Abstract : Immunoaffinity enrichment of peptides coupled to multiple reaction monitoring‐mass spectrometry (immuno‐MRM) enables highly specific, sensitive, and precise quantification of peptides and post‐translational modifications. Major obstacles to developing a large number of immuno‐MRM assays are poor availability of monoclonal antibodies (mAbs) validated for immunoaffinity enrichment of peptides and the cost and lead time of developing the antibodies de novo . Although many thousands of mAbs are commercially offered, few have been tested for application to immunoaffinity enrichment of peptides. In this study, we tested the success rate of using commercially available mAbs for peptide immuno‐MRM assays. We selected 105 commercial mAbs (76 targeting non‐modified "pan" epitopes, 29 targeting phosphorylation) to proteins associated with the DNA damage response network. We found that 8 of the 76 pan (11%) and 5 of the 29 phospho‐specific mAbs (17%) captured tryptic peptides (detected by LC‐MS/MS) of their protein targets from human cell lysates. Seven of these mAbs were successfully used to configure and analytically characterize immuno‐MRM assays. By applying selection criteria upfront, the results indicate that a screening success rate of up to 24% is possible, establishing the feasibility of screening a large number of catalog antibodies to provide readily‐available assay reagents.